2008
DOI: 10.1371/journal.pone.0001425
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular Absorption: A Bat Breaks the Mammal Paradigm

Abstract: Bats tend to have less intestinal tissue than comparably sized nonflying mammals. The corresponding reduction in intestinal volume and hence mass of digesta carried is advantageous because the costs of flight increase with load carried and because take-off and maneuverability are diminished at heavier masses. Water soluble compounds, such as glucose and amino acids, are absorbed in the small intestine mainly via two pathways, the transporter-mediated transcellular and the passive, paracellular pathways. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 56 publications
4
52
0
2
Order By: Relevance
“…Because the role of diet on paracellular nutrient absorption is not yet clear, and because previous studies focused on species that consume primarily carbohydrate-rich diets Tracy et al, 2007;Caviedes-Vidal et al, 2008;Brun et al, 2014), we examined species that all rely substantially on protein-rich diets. It was previously suggested that carnivores might rely more extensively on paracellular nutrient absorption than herbivores (McWhorter et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Because the role of diet on paracellular nutrient absorption is not yet clear, and because previous studies focused on species that consume primarily carbohydrate-rich diets Tracy et al, 2007;Caviedes-Vidal et al, 2008;Brun et al, 2014), we examined species that all rely substantially on protein-rich diets. It was previously suggested that carnivores might rely more extensively on paracellular nutrient absorption than herbivores (McWhorter et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…For these reasons, we determined fractional recovery by serial blood sampling (for details, see Caviedes-Vidal et al, 2008;Karasov et al, 2012). Individual bats were dosed with an oral gavage (in saline and 50 mmol l −1 glucose) or intraperitoneal injection (in saline), and a blood sample was taken from the antebrachial or uropatagial vein after ~5, 15, 30, 45, 60 and 90 min.…”
Section: Assessment Of Paracellular Absorption In Intact Animalsmentioning
confidence: 99%
“…Both flying and resting fruit bats can use ingested sugars as a direct fuel, just like hummingbirds (Amitai et al., 2010; Voigt & Speakman, 2007; Welch & Suarez, 2008). Additionally, an elevated amount of sugar intake is parallel with an increased speed of paracellular nutrient absorption in fruit bats (Caviedes‐Vidal et al., 2008; Tracy et al., 2007). Therefore, these bats can uptake large quantities of sugar each night.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, paracellular absorption accounts for 60-90% of the glucose absorption in all small birds and bats studied to date (Caviedes-Vidal et al, 2008;Caviedes-Vidal et al, 2007;Chediack et al, 2003;Tracy et al, 2007). In contrast, transporter-mediated absorption is much more important in terrestrial mammals (Lavin and Karasov, 2008;.…”
Section: Introductionmentioning
confidence: 99%